Pathological findings in an old female giant panda - a case report - Wu, Bangyuan (Slovenian veterinary research, 2022)
The giant panda (Ailuropoda melanoleuca) is one of the most endangered species in the world. Climate change and susceptibility to disease are two of the greatest threats to this species. We performed a necropsy and histopathological exami-nation of the organs of an old panda and investigated the pathogenesis associated with death. Necropsy and histopathological observation revealed some typical age-related lesions, such as cataract, atherosclerosis, renal insufficiency and splenic atrophy. We also confirmed hepatic lesions associated with parasitic infection. Overall, our observations revealed that the predominant cause of mortality in this panda was multiple organ dysfunction (MOD).
Keywords: Multiple Organ Failure; Ursidae